2008
DOI: 10.1002/da.20392
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-face versus remote administration of the Montgomery-Asberg Depression Rating Scale using videoconference and telephone

Abstract: Although the use of telemedicine in psychiatry has a long history in providing clinical care to patients, its use in clinical trials research has not yet been commonly employed. Telemedicine allows for the remote assessment of study patients, which could be done by a centralized, highly calibrated, and impartial cohort of raters independent of the study site. This study examined the comparability of remote administration of the Montgomery-Asberg Depression Rating Scale (MADRS) by videoconference and by telepho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 31 publications
(34 reference statements)
2
29
1
Order By: Relevance
“…On the other hand, Yoshino et al [75] observed statistically significantly lower ICC scores in the narrow bandwidth condition compared to the broad bandwidth in for BPRS scores. In a rigorous comparison of inter-rater reliability that reduced artificial inflation of reliability estimates by requiring interviewers to generate their own clarifying questions and probes, Kobak et al [66][67][68] observed very high reliability estimates between four psychiatrists at three different locations using the HAMD via telepsychiatry or FTF [67] . And although diagnostic assessments via telepsychiatry appear to be reliable even when using interpreters [60] , there are mixed results of the reliability of telepsychiatry assessments when visual information is required.…”
Section: Hubley S Et Al Telepsychiatry Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Yoshino et al [75] observed statistically significantly lower ICC scores in the narrow bandwidth condition compared to the broad bandwidth in for BPRS scores. In a rigorous comparison of inter-rater reliability that reduced artificial inflation of reliability estimates by requiring interviewers to generate their own clarifying questions and probes, Kobak et al [66][67][68] observed very high reliability estimates between four psychiatrists at three different locations using the HAMD via telepsychiatry or FTF [67] . And although diagnostic assessments via telepsychiatry appear to be reliable even when using interpreters [60] , there are mixed results of the reliability of telepsychiatry assessments when visual information is required.…”
Section: Hubley S Et Al Telepsychiatry Reviewmentioning
confidence: 99%
“…Two studies compared the accuracy of diagnoses made using the SCID [59,60] , two studies evaluated reliability of child assessments [42,61] , four studies evaluated reliability of neuropsychological assessments [62][63][64][65] , and three studies evaluated reliability of measures of depressive symptom severity [66][67][68] . The remaining studies evaluated a range of targets such as alcohol use severity [69] , diagnostic accuracy [70][71][72] , competency to stand trial [73] , psychosis [26] , and adult autism [21] .…”
Section: Hubley S Et Al Telepsychiatry Reviewmentioning
confidence: 99%
“…Comparing video-conferencing, telephone consultations and conventional face-to-face methods, satisfactory assessment was possible with all three modes for depression, using the Montgomery-Asberg Depression Rating Scale. 3 Telepsychiatry has also been successful in child psychiatry, depression, dementia, schizophrenia, suicide prevention, post-traumatic stress, panic disorders, substance abuse, eating disorders and smoking prevention. 4 …”
Section: Many Comparisons Have Been Made Between Telepsychiatricmentioning
confidence: 99%
“…The USQ has been used to evaluate how well subjects like the clinical content of computerized or Web-based applications. [22][23][24][25][26][27][28] It contains 15 statements, each of which is rated on a 4-point scale (strongly agree, agree, disagree, strongly disagree), and covers several dimensions of the user experience ( Table 1). Good internal consistency has been reported (Cronbach's alpha = 0.92).…”
Section: Methodsmentioning
confidence: 99%